Autonomy, pro-social behaviour, and working to the future: how coaches in the community can model "Next" practice for their participants. Issue 5 (3rd September 2021) - Crisp, Philippe
ABSTRACT: Rationale/purpose: There is an existing belief that community sport projects can contribute to positive developmental outcomes such as pro-social behaviours and community engagement. This study looks to establish the extent to which these types of sport projects might work, particularly in the way that they might deliver longer-lasting success for individuals' post sport programme journeys. Design/methodology/approach: Data were collected via semi-structured interviews with six community sport professionals/coaches who had experience of working on sport intervention projects based in deprived areas. Findings: The data illustrated how, through positive experiences, some of the community sport professionals' participants would continue in success-oriented directions post programme intervention. The findings suggest that allowing for educational opportunities (including non-traditional formats), promoting incremental levels of participant responsibility, and facilitating positive relationships through acting as positive adult role models can produce progressive and lasting change. Practical implications: The paper highlights the interdisciplinary nature of community sport and youth work, and suggests that coach education systems in the UK should consider embedding more youth work principles and practice. Research contribution: Using a qualitative approach, this paper presents the similarities and interface between the practice of community sport professionals/coaches and youth work.